Three Bold Pixies and Other Stories - Blyton, Enid; Illustrated by Cloke, Rene (London Award Publications Ltd., 2001)
A selection of short stories by Enid Blyton including Three Bold Pixies, The Squabblers, The Runaway Apples and Silly Little Goofy.
Include Illustrations
Keywords: Short stories -- Children's stories -- English fiction